2017
DOI: 10.1159/000481947
|View full text |Cite
|
Sign up to set email alerts
|

Rare Occurrence of an Intraocular Choroidal Solitary Fibrous Tumor/Hemangiopericytoma

Abstract: Purpose: Tumors previously diagnosed as solitary fibrous tumors (SFT) and hemangiopericytomas (HPC) are characterized by the NAB2-STAT6 fusion gene, leading to nuclear STAT6 expression, and are now considered part of one SFT/HPC tumor entity by the 2016 World Health Organization Classification of Tumors of the Central Nervous System. We present the first primary choroidal SFT/HPC with the diagnosis confirmed by STAT6 expression. Procedures: A 51-year-old man underwent enucleation for a choroidal mass, which re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…In the same year, the common gene fusion between NAB2 and STAT6 was discovered in SFT/HPC. The 2016 WHO Classification of Tumors of the Central Nervous System designated these tumors, characterized by the NAB2-STAT6 gene fusion, as SFT/HPC in mesenchymal/non-mesenchymal tumors ( 2 , 9 , 33 , 34 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the same year, the common gene fusion between NAB2 and STAT6 was discovered in SFT/HPC. The 2016 WHO Classification of Tumors of the Central Nervous System designated these tumors, characterized by the NAB2-STAT6 gene fusion, as SFT/HPC in mesenchymal/non-mesenchymal tumors ( 2 , 9 , 33 , 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…In 2013, three groups reported that SFT and HPC have a common gene fusion between NGFI-A-binding protein 2 (NAB2) and signal transducer and activator of transcription 6 (STAT6) (1,6,7). Thereafter, STAT6, which has dual functions as a signal transducer and as transcription activator in SFT and HPC, was recognized as the highly sensitive and specific immunohistochemical marker for SFT/HPC (2)(3)(4)(5)(8)(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 2 Intraocular SFT/HPCs are extremely rare, with only six cases previously reported. 3 , 5 , 6 , 7 , 8 , 9 Four of these cases report SFT/HPC arising from the choroid, 3 , 7 , 8 , 9 one reported supraciliary origin, 5 and the sixth reported ciliary body origin of the tumor. 6 None reported extrascleral extension.…”
Section: Introductionmentioning
confidence: 97%
“…In 2016 the World Health Organization Classification of Tumors of the Central Nervous System was revised to include SFT and HPC as the same neoplasm, now designated as SFT/HPC. 3 On histology, both SFT/HPC show a haphazard or “patternless” architecture, with HPC classically having “staghorn” branching vessels and SFT showing a spindle-cell matrix with “ropey” collagen. SFT/HPC which show a typical SFT pattern and less than 5 mitoses/10 HPF are considered grade I, those with an HPC pattern and less than 5 mitoses/10 HPF are grade II, and those with an HPC pattern and at least 5 mitoses/10 HPF are grade III.…”
Section: Introductionmentioning
confidence: 99%